BRACU new campus development project construction schedule (1.04.22-30.04.22) - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding construction schedule from 1 April, 2022 to 30 April, 2022 of BRACU new campus project.